Exploring the Vegetation Characteristics of Karst Landscapes: A Study of Community Forest in Tubokarto Village, Wonogiri, Indonesia - Prabowo, Sukma Hari; Rahmadwiati, Rissa; Nufus, Malihatun (Media Konservasi, 2024)
Karst landscapes are characterized by unique relief and drainage patterns, which influence the types of vegetation that can inhabit these environments. Vegetation in karst ecosystems plays a crucial role in groundwater filtration. Plant species diversity within these communities contributes to structural variations across different habitats. This study evaluates the potential of vegetation in community forests in Tubokarto Village, Wonogiri Regency, by analyzing species composition and vegetation. Using a purposive sampling method, we selected areas with polyculture planting patterns and agroforestry, applying a sampling intensity of 2.2% with 20 × 100 m strip plots. The results showed that the species composition at the location consisted of 18 species in 7 families. The stand density for trees is 221 ind ha–1, poles 436 ind ha–1, saplings 1,144 ind ha–1, and seedlings 2,650 ind ha–1. Tectona grandis emerged as the dominant species, with the highest Importance Value Index (IVI) values: 142.79 at the tree level, 212.48 for poles, 197.84 for saplings, and 122.29 for seedlings. Species diversity indices were 1.53 for trees, 0.97 for poles, 1.36 for saplings, and 1.21 for seedlings. The species richness index showed values of 2.79 for trees, 1.49 for poles, 1.21 for saplings, and 1.80 for seedlings, while the species evenness index ranged from 0.43 to 0.76. The vegetation structure of Tubokarto Village spans strata B and C, with tree diameter class distribution resembling that of natural forests. Environmental factors, including climate and soil composition, are likely influencing species growth patterns.